Love During Wartime - Bier, Gabriella (Sweden, 2011)
Unable to live together in their countries of birth, a newlywed couple, Jasmin (an Israeli Jew) and Osama (a Palestinian Muslim), look hopefully toward a future together in Germany. As they wait for Osama to receive a visa, both turn to their crafts as platforms for expression and catharsis. “Love During Wartime” follows a couple who is determined to transcend the boundaries of prejudice and fight against everything and everyone to find metaphorical and literal neutral ground.
Verzio Film Festival Submission
Duration: 01:32:00
Verzio Film Festival Submission
Keywords: Documentary films